Insulin degludec: four times lower pharmacodynamic variability than insulin glargine under steady-state conditions in type 1 diabetes - Heise, T.; Hermanski, L.; Nosek, L.; Feldman, A.; Rasmussen, S.; Haahr, H. (Diabetes, obesity & metabolism, 2012)
Aims Insulin degludec (IDeg) is a new‐generation basal insulin with an ultra‐long duration of action. We compared the pharmacodynamic (PD) variability of IDeg and insulin glargine (IGlar) under steady‐state conditions. Methods Day‐to‐day variability in glucose‐lowering effect was investigated in 54 subjects with type 1 diabetes who underwent a 24‐h euglycaemic glucose clamp on the 6th, 9th and 12th day of treatment with 0.4 U/kg of IDeg or IGlar once daily. Within‐subject variability was estimated using a linear mixed model on log‐transformed PD endpoints derived from the glucose infusion rate (GIR) profiles during the clamps. Results For IDeg the day‐to‐day variability in glucose‐lowering effect was four‐times lower than for IGlar for total metabolic effect (AUCGIR,0‐24h,SS, CV 20% vs. 82%) and for the last 22 h [AUCGIR,2‐24h,SS (not influenced by intravenous insulin during the clamp), CV 22% vs. 92%]. Furthermore, lower variability in the maximum effect was observed for IDeg vs. IGlar (GIRmax,SS, CV 18% vs. 60%). The lower within‐subject variability of IDeg was consistent over time (CVs of 33% for AUCGIR,0‐2h,SS, 32% for AUCGIR,10‐12h,SS and 33% for AUCGIR,22‐24h,SS), whereas the variability of IGlar was higher and increased substantially 8 h post‐dosing (CVs of 60% for AUCGIR,0‐2h,SS, 135% for AUCGIR,10‐12h,SS and 115% for AUCGIR,22‐24h,SS). Conclusions These results show that IDeg has a significantly more predictable glucose‐lowering effect from day to day than IGlar.